2013
DOI: 10.1021/bi4011978
|View full text |Cite
|
Sign up to set email alerts
|

Fe-S Cluster Biogenesis in Gram-Positive Bacteria: SufU Is a Zinc-Dependent Sulfur Transfer Protein

Abstract: The biosynthesis of Fe-S clusters in Bacillus subtilis and other Gram-positive bacteria is catalyzed by the SufCDSUB system. The first step in this pathway involves the sulfur mobilization from the free amino acid cysteine to a sulfur acceptor protein SufU via a PLP-dependent cysteine desulfurase SufS. In this reaction scheme, the formation of an enzyme S-covalent intermediate is followed by the binding of SufU. This event leads to the second half of the reaction where a deprotonated thiol of SufU promotes the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
87
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(102 citation statements)
references
References 42 publications
14
87
0
1
Order By: Relevance
“…5), whereas, in the absence of ATP, MnmA did not affect YrvO's cysteine desulfurase activity. This activity enhancement has also been observed for cysteine desulfurases in the presence of their corresponding sulfur acceptors and has been attributed to the ability of sulfur acceptor substrates to accelerate the regeneration of the enzyme for the next catalytic cycle through a rapid persulfide sulfur transfer (19,20,30,31). That is, the sulfur transfer step from YrvO to MnmA is faster than the reduction of YrvO's persulfide by DTT.…”
Section: Levels Of Expression Of Mnma Affects Abundance Of Smentioning
confidence: 58%
See 1 more Smart Citation
“…5), whereas, in the absence of ATP, MnmA did not affect YrvO's cysteine desulfurase activity. This activity enhancement has also been observed for cysteine desulfurases in the presence of their corresponding sulfur acceptors and has been attributed to the ability of sulfur acceptor substrates to accelerate the regeneration of the enzyme for the next catalytic cycle through a rapid persulfide sulfur transfer (19,20,30,31). That is, the sulfur transfer step from YrvO to MnmA is faster than the reduction of YrvO's persulfide by DTT.…”
Section: Levels Of Expression Of Mnma Affects Abundance Of Smentioning
confidence: 58%
“…In previous work, we and others showed that sufS is adjacent to its sulfur acceptor gene, sufU (17,18), coding for a zinc-dependent sulfur transfer protein (19). Both proteins are involved in the formation of Fe-S clusters.…”
mentioning
confidence: 99%
“…SufS is a cysteine desulfurase that catalyzes the removal of elemental sulfur from cysteine, producing alanine and a SufS-bound persulfide (15). The persulfide is transferred to SufU, which is a sulfur transfer protein that provides the sulfur to SufBCD (16). After synthesis, the Fe-S cluster is transferred directly to either an apoprotein or an Fe-S cluster carrier that traffics the cofactor to the target apoprotein (11,17).…”
mentioning
confidence: 99%
“…Another protein belonging to the SUF system is the Zn-dependent SufU [57], which is absent in the Gram-negative bacteria such as E. coli . SufU, a homolog of IscU, is able to complement SufE, as it happens in the case of Bacillus subtillis, Enterococcus faecalis, Thermatoga maritima and various mycobacteria [5861].…”
Section: Fe–s Cluster Machineries: a Brief Overviewmentioning
confidence: 99%